2016
DOI: 10.1080/14767058.2016.1191064
|View full text |Cite
|
Sign up to set email alerts
|

Blood product transfusions are associated with an increase in serum (1-3)-beta-d-glucan in infants during the initial hospitalization in neonatal intensive care unit (NICU)

Abstract: BDG is increased after RBC and FFP transfusions in neonates, leading to overdiagnosis of IFI. Fungal colonization status in peripheral sites and central cultures could help to reduce the risk of misdiagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…13,24 Indeed, some studied populations in false-positive BDG results as observed in previous studies. 7,8,25 Such factors included the use of cotton gauze during surgery, blood product transfusions, broad-spectrum antibiotics or antifungal therapy 8,17,18 and systemic bacterial infections. For example,…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…13,24 Indeed, some studied populations in false-positive BDG results as observed in previous studies. 7,8,25 Such factors included the use of cotton gauze during surgery, blood product transfusions, broad-spectrum antibiotics or antifungal therapy 8,17,18 and systemic bacterial infections. For example,…”
Section: Discussionmentioning
confidence: 99%
“…For example, Goudjil et al reported that blood product transfusion were associated with increased BDG value in neonates. 17…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations